Making information and communication technologies work for food security in Africa - Bertolini, Romeo (International Food Policy Research Institute, 2004)
Africa faces a difficult challenge in meeting the main target of the first Millennium Development Goal — to halve the number of people suffering from malnutrition and hunger by 2015. Bridging the digital divide through the development and use of information and communication technologies (ICTs)—such as fixed-line and mobile phones and Internet services—will not directly solve this challenge, but it can make a significant contribution. -- from Text